Impact of family home visits on medical students’ learning in the field of social pediatrics (2013)
ABSTRACT: This article reports the results from a study conducted among medical students at the University of Antioquia. Its aim was to assess the impact of family home visits that favored the processes of comprehensive training through meaningful learning. This was a qualitative-interpretative case study with systematization, using the following instruments: interviews, surveys, focus groups document analysis and participant observation (2006-2011). The results showed that when medical consultations were complemented with family home visits, students became sensitized, hich increased their motivation and activated their willingness to learn meaningfully. Additionally, it was demonstrated that family home visits presented links with an active didactic strategy that when implemented intentionally, had an impact on students’ humanist and social profile as future healthcare professionals. Application of this strategy is important for teaching social pediatrics and internal medicine.